The Portrait of Noken As A Manifestation of The Existence of Papuans - Yafed Syufi; Made Budiarsa; Wayan_Simpen; Made Sri Satyawati (e-Journal of Linguistics, 2019)
The Portrait of Noken as a manifestation of the Existence of Papuans is seen from theperspective of the socio-cultural aspect, Noken, as a manifestation of the indigenous Papuanrepresentation in its mandate, is only vague but its meaning is very deep. Its meanings can beboth denotative and connotative. For example, the Noken called mesin, as a medium oftransporting various types of goods, has a denotative meaning. In addition, it also has aconnotative meaning, namely a person who is open and likes giving whatever he/she has inhis/her Noken. The next connotative meaning is as a mother who carries the burden of life or as itis usually called ifaj uk aromat mowran (a women carrying a lot of burden), starting from theperiod of menstruation, conceiving, giving birth and breastfeeding, which is identical to a Nokencalled mesin. Unlike the case of Noken, which is called mecoi, this kind of Noken has two kindsof meanings, namely denotatively as a means of transporting goods and connotatively as aperson who is closed or stingy. Both mesin and mecoi are used for reducing the amount ofgarbage that has been wrapped around the life of the nation and the state.